SURGICAL MANAGEMENT OF BENIGN PROSTATIC HYPERPLASIA: A CONTEMPORARY NARRATIVE REVIEW OF TURP, HOLEP, THULEP, AND AQUABLATION - Stanisław Jurkowski; Konrad Zieliński; Jagoda Józefczyk; Karolina Ganczar; Paweł Buć; Karolina Buć; Mikołaj Zalewski; Marianna Rudzińska; Łukasz Krzystek; Michał Mazurek (International Journal of Innovative Technologies in Social Science, 2026)
Background: Benign prostatic hyperplasia (BPH) remains one of the most common causes of lower urinary tract symptoms in aging men. Surgical intervention is required when medical therapy becomes insufficient, and recent technological advancements have introduced several minimally invasive alternatives to traditional transurethral resection of the prostate (TURP). This review provides a contemporary comparison of TURP, holmium laser enucleation (HoLEP), thulium laser enucleation (ThuLEP), and Aquablation. Methods: A narrative review was conducted using a structured PubMed search with the query: "Benign Prostatic Hyperplasia" AND (TURP OR HoLEP OR ThuLEP OR Aquablation) AND "minimally invasive surgery". A total of 43 studies published between 1993 and 2025 were screened, and 15 met the inclusion criteria. Data on perioperative outcomes, functional results, complications, and retreatment rates were extracted and synthesized qualitatively. Results: TURP remains an effective reference procedure but presents higher bleeding risk, longer catheterization, and increased rates of sexual dysfunction compared with modern alternatives. HoLEP demonstrated superior symptom improvement, reduced blood loss, and durable efficacy across all prostate sizes. ThuLEP showed comparable functional outcomes and strong hemostatic performance. Aquablation offered robot-assisted precision with reduced thermal injury and favorable preservation of ejaculatory function, particularly in larger prostates. Each technique demonstrated clinically meaningful improvements in LUTS and urinary flow, with minimally invasive modalities generally offering more favorable perioperative profiles. Conclusions: Contemporary evidence supports the growing use of HoLEP, ThuLEP, and Aquablation as effective and often superior alternatives to TURP. Surgical selection should be individualized based on prostate size, patient comorbidities, sexual function priorities, and surgeon expertise. Further high-quality comparative studies are warranted.